Information System Design And Manufacture Online Booking Car Service Website Based And Spare Part Availability At CV. Bersama Maju Service Central Jakarta Branch - Rahmawati, Dwi; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2023)
CV. Bersama Maju Service is a company engaged in the field of car repair and maintenance services. At CV Bersama Maju Service the registration process for services is still done manually using paper besides that the data is still processed using Microsoft Excel and Microsoft Word so that it takes quite a long time and is considered inefficient, especially for storing the data. And to overcome all these obstacles a study was made entitled